New method of measuring subjective well-being: prospective validation study of the ‘Daily Experience Sampling Questionnaire’ (DESQ) in patients with psoriasis and healthy subjects in Germany - Blome, Christine; Kirsten, Natalia; Nergiz, Ibrahim; Schiffner, Ulrich; Otten, Marina; Augustin, Matthias (BMJ open, 2020)
ObjectivesTo validate the newly developed Daily Experience Sampling Questionnaire (DESQ) that measures affective subjective well-being (SWB). The DESQ is an end-of-day diary in which respondents retrospectively rate their SWB at six different, randomly determined moments; it is completed over 1 week. The DESQ shall provide an alternative or complementary approach to existing methods of near-time SWB measurement (experience sampling, Day Reconstruction Method). The primary research objective was to determine criterion validity of the DESQ.DesignProspective, non-interventional study.SettingParticipants were recruited in Hamburg, Germany, at a specialised outpatient clinic (patients) and via different channels (healthy participants).Participants101 adults with diagnosed and stable psoriasis (46 women, 55 men); 105 adults without psoriasis (49 women, 56 men).Primary and secondary outcome measuresParticipants completed the DESQ for 3 weeks. In weeks 2 and 3, they also performed experience sampling. Criterion validity was determined by weekwise intraclass correlations (ICC) between both methods. Sensitivity to change was determined by the correlation between changes in both methods from weeks 2 to 3. For convergent validity, related concepts such as life satisfaction were measured. Retest reliability was determined using DESQ values of weeks 2 and 3.ResultsCriterion validity was excellent (ICC: patients=0.86, 95% CI 0.81 to 0.91; healthy participants=0.86, 95% CI 0.79 to 0.91). Sensitivity to change was r=0.57 and r=0.56, respectively. Correlations with convergent criteria were mostly significant and higher in constructs more proximal to SWB. The ICC indicating retest reliability was 0.77 in patients (95% CI 0.68 to 0.84) and 0.81 in healthy participants (95% CI 0.73 to 0.86).ConclusionsThe DESQ is a valid, reliable and feasible instrument for SWB measurement in people with psoriasis and healthy people. Its approach of end-of-day evaluations of single moments may also lend itself to the measurement of other highly time-variant constructs such as pain, fatigue or depression.